"Occupying Nature: Fishing for Meaning in the Asian Carp". Issue 1 (April 2014) - Colón, Sigma
Abstract This article explores the ecological and social processes by which some species become invasive and the prominent environmental and commercial role they play as such. The deliberate introduction of non‐native species to novel environments is as old as the history of human migration but in recent years their accelerated movement globally made strikingly visible the impact of these nonhuman occupations of the natural world. Methods for dealing with the problem of invasive species highlight the interconnections among degraded ecologies, the social transformation of local environments, and processes of globalization. The example of the Asian carp demonstrates how the natural world intrudes on human infrastructure and landscapes, exceeding the uses to which humans endeavor to put it, occupying and altering the organic and built environment alike.